1999
DOI: 10.1074/jbc.274.49.34613
|View full text |Cite
|
Sign up to set email alerts
|

Expression of an Active, Monomeric Catalytic Domain of the cGMP-binding cGMP-specific Phosphodiesterase (PDE5)

Abstract: Phosphodiesterases (PDEs) comprise a superfamily of phosphohydrolases that degrade 3,5-cyclic nucleotides. All known mammalian PDEs are dimeric, but the functional significance of dimerization is unknown. A deletion mutant of cGMP-binding cGMP-specific PDE (PDE5), encoding the 357 carboxyl-terminal amino acids including the catalytic domain, has been generated, expressed, and purified. The K m of the catalytic fragment for cGMP (5.5 ؎ 0.51 M) compares well with those of the native bovine lung PDE5 (5.6 M) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 50 publications
5
46
0
Order By: Relevance
“…The crystal of PDE5A1 contains one catalytic domain in the crystallographic asymmetric unit, which apparently exists as a monomer. This is consistent with the biochemical studies that the monomeric fragment of bovine PDE5A (residues 508 -865) has similar catalytic activity as the full-length PDE5A (36). The electron density showed that residue 778 of PDE5A1 is better modeled with leucine instead of isoleucine in the wild type PDE5A1 sequence.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The crystal of PDE5A1 contains one catalytic domain in the crystallographic asymmetric unit, which apparently exists as a monomer. This is consistent with the biochemical studies that the monomeric fragment of bovine PDE5A (residues 508 -865) has similar catalytic activity as the full-length PDE5A (36). The electron density showed that residue 778 of PDE5A1 is better modeled with leucine instead of isoleucine in the wild type PDE5A1 sequence.…”
Section: Resultssupporting
confidence: 78%
“…A typical batch of purification yielded over 10 mg of PDE5A1 from a 2-liter cell culture. The fragment of human PDE5A1 expressed in E. coli had a catalytic activity of about 2 mol/min/mg, which is comparable with that of the protein expressed in a baculovirus system (36).…”
Section: Methodsmentioning
confidence: 58%
“…The basis for this effect is not known, but a leucine zipper motif (Ile 312 -X 6 -Leu 318 -X 6 -Glu 324 -X 6 -Leu 331 -X 6 -Ile 337 -X 6 -Leu 344 -X 6 -Ile 351 ) located in the segment of sequence between the GAFs might contribute. Disruption of this motif in PDE5 holoenzyme by site-directed mutagenesis does not produce monomerization (39). However, the high affinity of dimerization imparted by either GAF a or GAF b might mask a weakened interaction in this motif.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated C domains of PDEs are catalytically active, and some are monomers (103, 161-163, 168, 183, 184, 202, 327, 365, 398, 417, 418). In some cases, their kinetic char-acteristics are indistinguishable from those of the holoenzyme, whereas in other instances there are differences (40,103,297,298). Based on the x-ray crystal structure for a near full-length PDE2, Pandit et al (287) have proposed that autoinhibition is provided by physical constraints imposed by dimer contacts in the C domains and that activation occurs by disruption of that interface (Fig.…”
Section: B Oligomeric State Of Phosphodiesterasesmentioning
confidence: 99%